ASSOCIATION OF SERUM MAGNESIUM LEVELS WITH FASTING PLASMA GLUCOSE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS ON METFORMIN OR PIOGLITAZONE - Mudjanarko, Sony; Nasution, Huwainan (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The aim of this study is to analyze the association between serum magnesium level and fasting plasma glucose in patients with type 2 diabetes mellitus (DM) who had taken metformin or pioglitazone. METHODOLOGY Serum magnesium level and fasting plasma glucose were examined from a total of 41 patients whose type 2 diabetes was controlled with metformin ≥750 mg/day for at least 3 weeks or pioglitazone ≥15 mg/day for at least 4 weeks with a body mass index (BMI) of <30 kg/m2 . Fasting plasma glucose was analyzed using Roche/Hitachi Cobas C System. Serum magnesium level was analyzed using Roche/Hitachi Cobas C311/501 System. RESULTS The mean value of serum magnesium levels was 2.04±0.19 mg/dL. The median of fasting plasma glucose was 131±40, 85 mg/dL. The lower level of the serum magnesium had a significant correlation with fasting plasma glucose. CONCLUSION There is a significant negative correlation between the serum magnesium levels and fasting plasma glucose in type 2 DM on metformin or pioglitazone.